Setting Characteristics of Hydroxyapatite-Containing Glass Ionomer Cements by Oscillating Rheometer: Phosphate-based Compositions - Rawan Albeshti (Khalij-Libya Journal of Dental and Medical Research, 2025)
The purpose of this study was to assess the setting characteristics (working/setting times) of phosphate glass ionomer cement that were reinforced with different concentrations of hydroxyapatite crystals. A series of four ionomer glasses based on increasing in the phosphate content with general formula of 4.5SiO2-3Al2O3-xP2O5-3CaO-2CaF2 (Where x = 0.75, 1, 1.25 & 1.5) were synthesised using melt-quench route. Thereafter, the glass ionomer cements were prepared by mixing fine glass powder with poly-acrylic acid at specific powder to liquid ratio. The modified samples (hydroxyapatite-containing GICs) were made by adding hydroxyapatite powder to ionomer glass powder on weight substitution basis instead of certain amount of ionomer glass at a specific percentage of 0%, 5%, 10% and 15% respectively. The ionomer cements mixtures were investigated using Wilson’s Oscillating Rheometer in order to measure the setting characteristics (working/setting times) of the tested materials. Increasing in both phosphate content and substituted amount of hydroxyapatite for glass powder prolonged working/setting times of the glass ionomer cements significantly. The compositions with higher concentrations (15%) of hydroxyapatite showed adversely effect on handling properties and setting rates of the tested cements. The results suggest that addition of hydroxyapatite crystals has a significant impact on manipulation and setting reaction of the manufactured cements. The tested compositions with low-phosphate (highly reactive) and low-hydroxyapatite contents are more suitable for clinical use. Therefore, the additives concentrations’ have to be optimised to produce restorative materials with ideal properties.